Supplementation with an Inorganic Zinc Source in the Metalloproteomic Profile of Royal Jelly in Apis mellifera L. - de Almeida Longuini, Aimê [UNESP]; Martineli, Gabriel Moreno [UNESP]; Camilli, Marcelo Polizel [UNESP]; de Barros, Daniel Cavalcante Brambila [UNESP]; Vieira, José Cavalcante Souza [UNESP]; de Magalhães Padilha, Pedro [UNESP]; de Oliveira Orsi, Ricardo [UNESP] (Springer Nature, 2021)
This study aimed to evaluate the quality of royal jelly produced by honeybees Apis mellifera supplemented with different concentrations of inorganic zinc (zinc sulfate monohydrate—0, 25, 50, and 75 ppm). Two-dimensional electrophoresis for the fractionation of royal jelly proteins was performed, and the zinc level was quantified by the flame atomic absorption spectrometry (FAAS) technique. Proteins were identified by electrospray ionization mass spectrometry (ESI MS MS). Analysis of variance followed by the Tukey test (P < 0.05) was used. Supplementation with the mineral zinc positively affected the quantification of proteins for treatments 50 and 75 ppm. However, all treatments independent of zinc concentrations showed fewer protein spots when compared to the control. All zinc-containing proteins were classified as major royal jelly proteins (MRJPs). The exposure of nursing bees to the mineral zinc in its inorganic form reduced the expression of six different MRJPs involved in larval and glands development of nursing bees (MRJP1, MRJP2, MRJP3, MRJP5, and MRJP7), however promoted an increase in the expression of royal jelly proteins involved in defense systems (MRJP8 and MRJP9). The results demonstrate that vital proteins and metabolic processes are impaired in nursing bees exposed to the mineral zinc in its inorganic form in all doses used affecting nutrition and maintenance of colonies.
Keywords: Bees; Mineral; Proteomic; Supplementation